Molecular sieve SSZ-117x with high acidity
By embedding boron in the SSZ-117x molecular sieve and replacing it with aluminum, the problem of insufficient acid sites of existing zeolite materials was solved, which significantly improved the catalytic performance and achieved a more efficient organic compound conversion reaction.
Patent Information
- Application Number
- CN202380043818.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing zeolite materials lack sufficient acid sites in the catalytic organic compound conversion reaction, resulting in insufficient catalytic performance, and conventional methods are prone to losses of amorphous phase and Al acid sites during the preparation process.
By using N,N,N,3,5-pentamethyladamantane-1-ammonium cation as structural guide, SSZ-117x molecular sieve was synthesized using boron path, first embedded boron, and then replaced boron with aluminum to increase the acid of the molecular sieve Site to form an acid-rich SSZ-117x molecular sieve.
Relatively increasing acid sites and acidity are achieved, the catalytic characteristics of the molecular sieve are improved, and more efficient catalytic performance is provided, especially in the organic compound conversion reaction, which significantly improves the catalytic effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 365,514, filed on May 31, 2022, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present invention relates to a novel synthetic crystalline molecular sieve having increased acidity, designated SSZ-117x, and its synthesis. Background Art
[0004] Zeolite materials are known to have utility as adsorbents and to have catalytic properties for various types of organic compound conversion reactions. Certain zeolite materials are ordered porous crystalline materials having a well-defined crystalline structure determined by X-ray diffraction in which there are a large number of small cavities that may be interconnected by a number of smaller channels or pores. The size of these cavities and pores is uniform in a particular zeolite material. Because the size of these pores may allow the acceptance of adsorbed molecules of certain sizes while rejecting those of larger sizes, these materials are referred to as "molecular sieves," and these properties are exploited in various ways.
[0005] There are more than 250 known zeolite framework structures currently approved by the International Zeolite Association. In order to improve the performance of many organic compound conversions and adsorption processes, it is necessary to have new structures with properties different from known materials. Each structure has unique holes, channels and cage sizes, which give it specific properties as described above. Each framework structure also has a specific composition. The improvement in preparing purer single-phase materials is always important. Molecular sieves with increased acid sites are provided and can be valuable in catalyzing organic compound conversion reactions. Summary of the invention
[0006] According to the present invention, a crystalline molecular sieve with increased acid sites, called SSZ-117x, has been synthesized using N,N,N,3,5-pentamethyladamantan-1-ammonium cation as a structure directing agent (SDA). The synthesis is carried out through a boron route, and the final molecular sieve contains some boron. In one embodiment, the amount of boron may be 50-250ppm.
[0007] The SSZ-117x molecular sieves of the present invention have increased acid sites, and therefore increased acidity, and may have a chemical composition comprising the following molar relationship.
[0008] Table 1
[0009] wherein T is a tetravalent element including silicon and germanium. The SSZ-117x of the present invention also has relatively increased acid sites and some boron in the framework. SiO2 / GeO 2 The ratio may also be from 4 to 12, or from 7 to 10 in one embodiment.
[0010] In one embodiment, a method for synthesizing a molecular sieve having increased acidity as described herein is provided. The method comprises: (a) providing a reaction mixture comprising: (1) a FAU framework type zeolite; (2) a germanium source; (3) a boron source; (4) N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide (Q); (5) a fluoride ion source; and (6) water, and (b) then subjecting the reaction mixture to crystallization conditions sufficient to form SSZ-117x boron molecular sieve crystals.
[0011] The boron-containing molecular sieve is then treated to remove the structure directing agent (SDA), which is indicated above as Q. SDA can be removed by calcination, or by ozone treatment, for example at 150° C. It has also been found that treatment of the molecular sieve with dimethylformamide can remove SDA.
[0012] Once the SDA is removed, the boron-containing SSZ-117x molecular sieve is treated to replace the boron in the framework with aluminum. The molecular sieve with increased acid sites is then recovered. The molecular sieve is SSZ-117x enriched in acid sites.
[0013] In yet another aspect, a method of converting a feedstock comprising an organic compound to a conversion product is provided, the method comprising contacting the feedstock under organic compound conversion conditions with a catalyst comprising the SSZ-117x molecular sieve having increased acid sites as described herein.
[0014] Among other factors, the method of the present invention allows to obtain the SSZ-117x molecular sieve with increased acid sites. With the acid sites increased, it is meant that by using the method of the present invention and its boron path, the SSZ-117x molecular sieve can be obtained, the acid sites of the SSZ-117x molecular sieve being more than the possible acid sites of the molecular sieve with aluminum sites and no boron sites prepared by conventional direct methods. When adopting conventional routes, it has been found that some amorphous phases occur, so the loss of Al acid sites occurs. It has been quite surprisingly found that by first embedding boron into the framework, and then replacing boron with aluminum, the SSZ-117x molecular sieve with the acid sites of the relative increase number can be obtained. Therefore, the SSZ-117x molecular sieve is rich in acid or has the acidity of increase. The acid sites increased can cause the improvement of the catalytic properties of the SSZ-117x molecular sieve of the present invention. The SSZ-117x molecular sieve of the present invention also contains some boron. DETAILED DESCRIPTION
[0015] definition
[0016] The term "framework type" has the meaning as given in Ch. Baerlocher and LB McCusker and DH Olsen in "Atlas of Zeolite Framework Types" (Elsevier, 6th revised edition, 2007).
[0017] The term "zeolite" generally refers to a synthetic aluminosilicate molecular sieve having a framework composed of aluminum oxide and silicon dioxide (i.e., repeating SiO 4 and AlO 4 tetrahedral unit).
[0018] The term "aluminogermanosilicate" refers to a crystalline microporous solid comprising aluminum, germanium and silicon oxides in its framework structure. The aluminogermanosilicate may be a "pure aluminogermanosilicate" (i.e., no other detectable metal oxides are present in its framework structure) or may be optionally substituted. When described as "optionally substituted," each framework may contain other atoms (e.g., B, Ga, In, Fe, Ti, Zr) that replace one or more atoms not already present in the parent framework.
[0019] The term "as-synthesized" is used herein to refer to the form of the molecular sieve after its crystallization and before the removal of the structure directing agent.
[0020] The term "anhydrous" is used herein to refer to a molecular sieve that is substantially free of both physically adsorbed water and chemically adsorbed water.
[0021] As used herein, the numbering scheme for the Periodic Table Groups is as disclosed in Chem. Eng. News 1985, 63(5), 26-27.
[0022] By "increase" or "more" acid sites is meant that the SSZ-117x molecular sieve prepared by the method of the present invention comprises more acid sites than the possible acid sites of the molecular sieve conventionally prepared without adopting the boron path of the present invention. When adopting conventional, direct methods using aluminum, it has been found that an amorphous phase occurs, which causes the loss of Al acid sites. It has been quite surprisingly found that by first embedding boron into the SSZ-117x framework, and then replacing boron with aluminum, a SSZ-117x molecular sieve is obtained, which has a relatively more aluminic acid sites than the aluminic acid sites obtained if boron is not introduced in the initial preparation of the molecular sieve. This increased acidity can affect and improve the catalytic properties of the molecular sieve. The molecular sieve will be quite useful, for example, in converting a raw material containing an organic compound into a conversion product. Due to the boron path, some boron still remains in the SSZ-117x molecular sieve.
[0023] Synthesis of molecular sieves
[0024] The molecular sieve SSZ-117x of the present invention is synthesized using a boron route. The method comprises: (a) providing a reaction mixture comprising (1) a silicon oxide source, such as a FAU framework type zeolite; (2) a germanium source; (3) a boron source; (4) N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide (Q); (5) a fluoride ion source; and (6) water; and then (b) subjecting the reaction mixture to crystallization conditions sufficient to form SSZ-117x boron molecular sieve crystals. In one embodiment, the FAU framework zeolite has only a small amount of Al 2 O 3 .SiO 2 / Al 2 O 3 The ratio of may be 300 or more. Therefore, the framework contains a large amount of boron.
[0025] SDA is removed from the molecular sieve, for example, by calcination or ozone treatment, and the molecular sieve is then treated to replace at least some, if not most, of the boron sites with aluminum. The SSZ-117x molecular sieve having increased acid sites can then be recovered.
[0026] The reaction mixture may have a molar ratio composition within the range shown in Table 2:
[0027] Table 2
[0028] wherein T and Q are as described above.
[0029] Suitable silica sources may include any suitable known sources such as colloidal silica, fumed silica, precipitated silica or alkali metal silicates. FAU framework type zeolites such as zeolite Y may also be a silica source. In such cases, the FAU framework type zeolite has a very high SiO of at least 250 and preferably at least 300 (e.g., 300 to 500). 2 / Al 2 O 3 molar ratio. The FAU framework type zeolite may contain two or more zeolites having different SiO 2 / Al 2 O 3 The FAU framework type zeolite may be zeolite Y or any of its various post-synthesis modifications, as known in the art.
[0030] The germanium source may include germanium oxide and germanium alkoxide (eg, germanium ethoxide, germanium isopropoxide).
[0031] Silicon and germanium can be 4 to 12 (e.g., 6 to 10) SiO 2 / GeO 2 The molar ratio exists in the reaction mixture.
[0032] The boron source may include boric acid, which is preferred. Other suitable sources may also be used, but are less preferred.
[0033] Fluoride ion sources may include, for example, hydrogen fluoride, ammonium fluoride, and ammonium bifluoride.
[0034] SSZ-117x with boron is synthesized using a structure directing agent comprising an N,N,N,3,5-pentamethyladamantan-1-ammonium cation (Q+) represented by the following structure (1):
[0035]
[0036] The reaction mixture typically has a Q / F molar ratio of 0.80 to 1.20 (eg, 0.85 to 1.15, 0.90 to 1.10, 0.95 to 1.05, or 1 to 1).
[0037] The reaction mixture may contain seed crystals of a molecular sieve material, such as boron SSZ-117x from a previous synthesis, in an amount of 0.01 to 10000 ppm by weight (e.g., 100 to 5000 ppm by weight) of the reaction mixture. Seeding may be advantageous in reducing the amount of time required for complete crystallization to occur. Additionally, seeding may result in an increase in the purity of the product obtained by promoting nucleation and / or formation of boron SSZ-117x on any undesired phases.
[0038] It has been noted that the reaction mixture components can be supplied from more than one source. Likewise, two or more reaction components can be supplied from one source. The reaction mixture can be prepared in batches or continuously.
[0039] The reaction mixture may be prepared batchwise or continuously, and the crystal size, morphology and crystallization time of the molecular sieves described herein may vary depending on the nature of the reaction mixture and the crystallization conditions.
[0040] Crystallization and post-synthesis processing
[0041] Consistent with the boron route, crystallization of the molecular sieve from the above reaction mixture can be carried out in a suitable reactor vessel (e.g., a polypropylene tank or a Teflon™-lined or stainless steel autoclave) under static, tumbling or stirring conditions at a temperature of 125° C. to 200° C. (e.g., 150° C. to 170° C.) for a time sufficient for crystallization to occur at the temperature used (e.g., 1 day to 20 days, or 2 days to 10 days). The hydrothermal crystallization process is typically carried out under pressure, such as in an autoclave, and is preferably carried out under autogenous pressure.
[0042] Once the boron-containing molecular sieve crystals are formed, the solid product can be recovered from the reaction mixture by conventional mechanical separation techniques such as centrifugation or filtration. The recovered crystals are washed with water and then dried to obtain the first synthesized SSZ-117x boron molecular sieve crystals. The drying step can be carried out at an elevated temperature (e.g., 75° C. to 150° C.) for several hours (e.g., about 4 to 24 hours). The drying step can be carried out under vacuum or normal pressure.
[0043] As a result of the crystallization process, the recovered crystalline molecular sieve product contains in its pore structure at least a portion of the structure directing agent used in its synthesis.The as-synthesized molecular sieve may be subjected to treatment to remove some or all of the structure directing agent used in its synthesis.
[0044] Removal of the structure directing agent can be carried out by heat treatment (e.g., calcination), in which the initially synthesized molecular sieve is heated at a temperature sufficient to remove some or all of the structure directing agent. Although pressures below atmospheric pressure can be used for heat treatment, atmospheric pressure is desirable for convenience. The heat treatment can be carried out at a temperature of at least 370°C for at least one minute and generally not more than 20 hours (e.g., 1 to 12 hours). The heat treatment can be carried out at a temperature of up to 925°C. For example, the heat treatment can be carried out at a temperature of 400°C to 600°C in the presence of an oxygen-containing gas.
[0045] Additionally or alternatively, the structure directing agent can be removed by ozone treatment. See, for example, AN Parikh et al., Micropor. Mesopor. Mater. 2004, 76, 17-22. In one embodiment, the use of ozone is preferred because it provides a higher micropore volume. It has also been found that SDA can be removed by treatment with dimethylformamide, for example at about 150°C.
[0046] The molecular sieve crystals can then be treated to replace at least some of the boron with aluminum, although it is preferred to replace most (at least 90%) of the boron, if not nearly all of the boron. In one embodiment, the amount of boron remaining after the exchange procedure can be 50 to 250 ppm of boron. Conventional techniques such as ion exchange can be used. However, treating the molecular sieve with an aqueous solution of aluminum nitrate is a preferred way to replace boron in the framework with aluminum. Treatment can be accomplished by contacting the molecular sieve with an aluminum nitrate solution under reflux.
[0047] Characterization of Molecular Sieve
[0048] The final SSZ-117x molecular sieve has a composition comprising the following molar relationship:
[0049] Al 2 O 3 :(n)TO 2
[0050] wherein n≥150; and T is a tetravalent element including silicon and germanium. In one embodiment, n in the foregoing relationship is 300 or greater, and in one embodiment n is 300 to 600.
[0051] The molecular sieve may have a chemical composition comprising the following molar relationships shown in Table 1:
[0052] Table 1
[0053] wherein T is a tetravalent element including silicon and germanium. The SSZ-117x of the present invention also has relatively increased acid sites and some boron in the framework. SiO 2 / GeO 2 The ratio may also be from 4 to 12, or in one embodiment from 7 to 10.
[0054] Acid-added SSZ-117x has a powder XRD diffraction pattern including the following peaks:
[0055] Table 3
[0056] (a) ±0.30 degrees
[0057] (b) The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = moderate (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).
[0058] As will be appreciated by those skilled in the art, the determination of the parameter 2-theta (2θ) is subject to both human and mechanical error, the combination of which can impose an uncertainty of approximately ±0.30° on each reported 2-theta value. o ) is recorded as the ratio of the peak intensity to the intensity of the strongest peak, which is assigned a value of 100. The relative intensities of the d-spacings are represented by the designations VS, S, M, and W, which represent very strong, strong, medium, and weak, respectively. In terms of relative intensity, the above designations are defined as: W (weak) <20; M (medium) is >20 and <40; S (strong) is >40 and <60; and VS (very strong) is >60. When the intensity is close to the end points of the range, the intensity can be characterized as being in any range. For example, an intensity of 18-22 can be listed as WM. However, due to the variation in the intensity of the lines, as is known in the art, one or more lines may have intensities that are in adjacent ranges.
[0059] The powder X-ray diffraction patterns presented herein were collected by conventional techniques. The radiation was CuKα radiation. The peak heights and positions as a function of 2θ (where θ is the Bragg angle) were read from the relative intensities of the peaks (adjusting for background), and d (corresponding to the inter-plane spacing of the recorded lines) was calculated.
[0060] Slight changes in the diffraction pattern can be attributed to changes in the molar ratio of the framework material of the sample, which is due to changes in the lattice constant. In addition, disordered materials and / or sufficiently small crystals will affect the shape and intensity of the peaks, resulting in significant peak broadening. Slight changes in the diffraction pattern can also be attributed to changes in the organic compounds used in the preparation. Calcination can also cause small shifts in the XRD pattern. Despite these minor perturbations, the basic lattice structure remains unchanged.
[0061] The increased acidity of the molecular sieve of the present invention can be measured, for example, by measuring its Bronsted acidity.
[0062] Adsorption and catalysis
[0063] The molecular sieve SSZ-117x of the present invention (wherein some or all of Q+ is removed) can be used as an adsorbent or catalyst to catalyze a variety of organic compound conversion processes, including many current conversion processes with commercial / industrial importance. The example of chemical conversion process (which is effectively catalyzed by the acid-rich SSZ-117x itself or by its combination with one or more other catalytically active materials (including other crystalline catalysts)) includes those requiring a catalyst or catalytic metal with acid activity. The example of organic conversion process that can be catalyzed by the acid-rich SSZ-117x includes cracking, hydrocracking, disproportionation, alkylation, oligomerization, aromatization and isomerization. The molecular sieve can also be used for exchanging heavy metals such as copper, which can be used to reduce nitrous oxide pollutants.
[0064] As in the case of many catalysts, it may be desirable to introduce into acid-rich SSZ-117x other materials that tolerate the temperature and other conditions used in the organic conversion process. Such materials include active and inactive materials and synthetic or naturally occurring zeolites and inorganic materials such as clay, silicon dioxide and / or metal oxides such as aluminum oxide. The latter may be naturally occurring, or in the form of a gelatinous precipitate or gel, including a mixture of silicon dioxide and metal oxides. The material (which is active) is used in combination with acid-rich SSZ-117x (i.e., combined with it or present during the synthesis of new materials) often changes the conversion rate and / or selectivity of the catalyst in some organic conversion processes. Inactive materials are suitable as diluents to control the conversion amount in a given process, so that the product can be obtained in an economical and orderly manner without adopting other means of controlling the reaction rate. These materials can be introduced into naturally occurring clays (e.g., bentonite and kaolin) to improve the crushing strength of the catalyst under commercial operation conditions. These materials (i.e., clay, oxides, etc.) serve as a binder for the catalyst. It is desirable to provide a catalyst with good crush strength because, in commercial use, it is desirable to prevent the catalyst from breaking into a powdery material.These clay and / or oxide binders are usually used for the sole purpose of improving the crush strength of the catalyst.
[0065] Naturally occurring clays (which can be composited with SSZ-117x) include the montmorillonite and kaolin families, which include sub-bentonites, and the commonly known kaolins such as Dixie, McNamee, Georgia and Florida clays or other clays in which the major mineral components are halloysite, kaolinite, dickite, nacrite or anthracite. Such clays can be used in their original state, such as as mined, or they can be initially subjected to calcination, acid treatment or chemical modification. Binders that can be used to composite with the acid-enriched SSZ-117x of the present invention also include inorganic oxides such as silicon dioxide, zirconium oxide, titanium oxide, magnesium oxide, beryllium oxide, aluminum oxide and mixtures thereof.
[0066] In addition to the aforementioned materials, the acid-rich SSZ-117x can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.
[0067] The relative proportions of the acid-rich SSZ-117x and the inorganic oxide matrix can vary widely, with the SSZ-117x content ranging from 1 to 90 wt % (eg, 2 to 80 wt %) of the composite. Example
[0068] The following illustrative examples are intended to be non-limiting. Example 1
[0069] Synthesis of N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide
[0070] 3,5-Dimethyladamantan-1-amine was permethylated with more than 3 times excess methyl iodide and 2 equivalents of potassium bicarbonate in methanol for several days. The reaction mixture was concentrated under reduced pressure and the resulting solid was extracted with 2 times chloroform. The chloroform was rotary evaporated under reduced pressure to recover the crude product. The crude product was recovered by stripping off the chloroform. The crude product was heated at 70°C in a minimum amount of 95% ethanol to produce a clear solution. The solution was cooled to room temperature to provide the iodide salt in the form of very clean crystals. The product was then purified by chemical analysis and in CDCl 3 The purity of the product was checked by H NMR and C NMR.
[0071] The resulting iodide salt was exchanged to the corresponding hydroxide salt by stirring it with a hydroxide exchange resin (AMBERLITE© IRN78) in deionized water overnight. The solution was filtered and the filtrate was analyzed for hydroxide concentration by titrating a small sample with a 0.1 N HCl standard solution. Example 2
[0072] Synthesis of SSZ-117x with Boron
[0073] 0.27 g of Tosoh 390HUA Y-zeolite (SiO 2 / Al 2 O 3 The molar ratio is about 500), 0.05g GeO 2 , 0.02 g of H 3 BO 3 and 2.5 mmol of N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide aqueous solution. The reactor was then placed in a fume hood and the water was evaporated to allow H 2 O / (SiO 2 +GeO 2 ) molar ratio was 7 (determined by the total mass of the suspension). Then, HF (2.5 mmol) was added, and the reactor was heated to 160° C. and tumbled at 43 rpm for about 7 days. The solid product was recovered by centrifugation, washed with deionized water and dried at 95° C.
[0074] Powder XRD will show the final product to be a new phase in pure form, called SSZ-117x Boron, and exhibit the characteristic peaks of Table 3. Example 3
[0075] Acid-enhanced SSZ117x
[0076] After all or part of the SDA is removed by calcination or ozone treatment, the recovered product is then treated with aqueous aluminum nitrate at reflux to provide the final SSZ-117x product, which has increased acid sites and also contains some boron. Example 4
[0077] Bronsted acidity
[0078] The Bronsted acidity of the molecular sieve of Example 3 was determined by temperature programmed desorption (TPD) of n-propylamine adapted from the description published by TJ GricusKofke et al. (J. Catal. 1988, 114, 34-45); TJ GricusKofke et al. (J. Catal. 1989, 115, 265-272); and JG Ittensor et al. (J. Catal. 1992, 138, 714-720). The sample was heated at 400°C to 500°C in flowing dry H 2 The dehydrated sample was then cooled to 120°C in flowing dry helium and kept at 120°C for 30 minutes in flowing helium saturated with n-propylamine for adsorption. The n-propylamine saturated sample was then heated to 500°C at a rate of 10°C / min in flowing dry helium. The Bronsted acidity was based on the weight loss versus temperature determined by thermogravimetric analysis (TGA) and the effluent NH 3 The Bronsted acidity of the sample is 77.72 μmol / g, which indicates that aluminum sites are introduced into the framework of the molecular sieve. Example 5
[0079] The as-synthesized boron SSZ-117x of Example 2 was heated in excess dimethylformamide at 150°C in a closed reactor for 5 days. After cooling, the solid was washed to be free of solvent, and then washed with water and dried at 95°C. The mass loss of this extraction was 20%. The dried solid was then subjected to ozonolysis at 150°C overnight to remove any residual SDA in the pores. The open structure now has a greatly changed XRD pattern, shown in Table 3.
[0080] Table 3
[0081] (a) ±0.30 degrees
[0082] (b)The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = moderate (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).
[0083] The product of the ozone treatment can then be treated to replace the boron with aluminum, for example by refluxing with aqueous aluminum nitrate.The resulting molecular sieve is SSZ-117x with boron and increased acid sites.
[0084] As used herein, the words "comprising" are intended to be an open-ended transition, meaning the inclusion of the recited elements but not necessarily the exclusion of other unrecited elements. The phrase "consisting essentially of is intended to mean the exclusion of other elements having any critical importance to the composition. The phrase "consisting of is intended to be a transition, meaning the exclusion of all elements other than the recited elements, except for only trace amounts of impurities.
[0085] To the extent not inconsistent with this document, all patents and publications referenced herein are hereby incorporated by reference. It will be understood that some of the above-mentioned structures, functions, and operations of the above-mentioned embodiments are not necessary for practicing the present invention, and are included in the specification only for the completeness of exemplary embodiments or embodiments. In addition, it will be understood that the specific structures, functions, and operations set forth in the above-mentioned referenced patents and publications can be practiced in conjunction with the present invention, but they are not essential to its practice. Therefore, it should be understood that the present invention can be practiced as specifically described without actually departing from the spirit and scope of the present invention defined by the appended claims.
Claims
1. A molecular sieve having a powder X-ray diffraction pattern comprising the following peaks: And wherein the molecular sieve comprises boron and has increased acid sites.
2. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: <h2 style=";text-align:left;direction:ltr">Al2O3:<h2 style=";text-align:left;direction:ltr"> (n) <h2 style=";text-align:left;direction:ltr"> TO2 wherein n≥150; and T is a tetravalent element including silicon and germanium.
3. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: <h2 style=";text-align:left;direction:ltr">Al2O3:<h2 style=";text-align:left;direction:ltr"> (n) <h2 style=";text-align:left;direction:ltr"> TO2 wherein n≥300; and T is a tetravalent element including silicon and germanium.
4. The molecular sieve according to claim 1, having a chemical composition comprising the following molar relationship: Wherein T is a tetravalent element including silicon and germanium. The molecular sieve according to claim 1 , wherein the amount of boron in the molecular sieve is 50-250 ppm.
6. A method for synthesizing the molecular sieve according to claim 1, the method comprising: (a) providing a reaction mixture comprising: (1) FAU framework type zeolite having a SiO2 / Al2O3 molar ratio of 300 or more; (2) Germanium source; (3) Boron source; (4) N,N,N,3,5-pentamethyladamantane-1-ammonium hydroxide (Q); (5) a fluoride ion source; and (6) Water; (b) subjecting the reaction mixture to crystallization conditions sufficient to form boron-containing molecular sieve crystals; (c) removing Q from the molecular sieve framework; and (d) Substituting aluminum for some of the boron in the molecular sieve crystals.
7. The method of claim 6, wherein the reaction mixture has the following composition expressed in molar ratio: Wherein T is a tetravalent element including silicon and germanium.
8. The method of claim 6, wherein the reaction mixture has the following composition expressed in molar ratio: Wherein T is a tetravalent element including silicon and germanium.
9. The method of claim 6, wherein the FAU framework-type zeolite is zeolite Y or a post-synthetically modified form of zeolite Y.
10. The method of claim 6, wherein the crystallization conditions comprise a temperature of 125°C to 200°C.
11. The process of claim 6, wherein the Q / F molar ratio of the reaction mixture is from 0.8 to 1.
2.
12. The method according to claim 6, wherein the Q is removed by calcination.
13. The method according to claim 6, wherein the Q is removed by treatment with ozone.
14. The method of claim 6, wherein replacing boron with aluminum comprises refluxing the molecular sieve crystals with an aluminum nitrate solution.
15. A method of converting a feedstock comprising an organic compound into a conversion product, the method comprising contacting the feedstock with a catalyst comprising the molecular sieve of claim 1 under organic compound conversion conditions.
16. A method of converting a feedstock comprising an organic compound into a conversion product, the method comprising contacting the feedstock with a catalyst comprising the molecular sieve of claim 4 under organic compound conversion conditions.
17. A method of ion exchanging metals, the method comprising contacting a stream comprising heavy metals with the molecular sieve of claim 1.
18. A process for ion exchanging metals, the process comprising contacting a stream comprising heavy metals with the molecular sieve of claim 4.
19. A product prepared by the method of claim 6.
20. A product prepared by the method of claim 14.
